THE MEANING EXTENSION OF OVER: A CRITIQUE OF KEY THEORIES - Long, Do Tuan; Huyen Trang, Vu Thi (VNU Journal of Foreign Studies, 2020)
This paper summarizes different approaches to the meaning extension of the English preposition over and proposes a multimodal approach comprising three spatial image theories and one mental space theory in reference to an image-based view. It is concluded that the author’s proposal is a combination of Deane’s 2005 multimodal spatial representations and  2017 Kövecses’s model, in which there is an emphasis that treating the spatial configurations of a spatial marker requires different frames and when the marker denotes a non-spatial sense, there exists an activation of a metaphor layered from its frame in certain context with a specific communicative purpose to the domain of which the frame is a part and finally the activation will reach the image schema that supports the frame.